Hidden programme and application development in web-based education - Sevindik, Tuncay; Gurol, Aysun; Kayisli, Korhan; Basal, Ahmet (Elsevier Science Bv, 2010)
Internet, gradually increasing its value in educational environments nowadays, is accepted to lead the web based education environments with semantic web applications, web mining and artificial nerve network. In web-based environments, hidden programme is needed to meet the needs of students emerging in the process. In this study, it is aimed to develop hidden programme applications for web based education and to determine the standards of this programme. To this end, how search motors and other elements give way to hidden programme was determined that In this study, local and global search engines along with forums were included in the sample of the study with random selection. (C) 2010 Elsevier Ltd. All rights reserved.
2nd World Conference on Educational Sciences (WCES-2010) -- FEB 04-08, 2010 -- Bahceschir Univ, Istanbul, TURKEY
Keywords: Internet; search enginees; hidden programme; web; distance education